An encumbered regional power? : the capacity gap in South Africa' s peace diplomacy in Africa - Kagwanja, Peter (Cape Town, South Africa : HSRC Press, 2009)
The main focus of this paper is the link between South Africa's gran d pan-African ambitions, especially in the area of peace, security and governance, and its own capacity to pursue these objectives. Specifical ly, the paper examines Pretoria's involvement in Africa, and its intern al capacity to support its mediation, peacekeeping and strengthening of the abilities of African institutions for peacemaking. Further, it exa mines the challenges posed by tension between its pan-African and econo mic interests as well as power rivalry at the continental level, which have greatly limited its ability to play a more assertive role in regio nal political and economic developments. Since its transition from apar theid to democracy in April 1994, South Africa has been an increasingly important player in peace promotion activities across the continent. B ecause of its moral power arising from its unique transition from apart heid to democracy, and its military and economic might, South Africa is widely viewed as being in the same league as other global middle-sized powers, and as a regional 'superpower'.
Includes bibliographical references (p. 33-36).
Keywords: Peace-building -- Africa, Southern; International relations; Peacekeeping forces -- Africa, Southern; Peace movements -- Law and legislation -- Africa, Southern